2001
DOI: 10.1073/pnas.241510898
|View full text |Cite
|
Sign up to set email alerts
|

Host cell factor requirement for hepatitis C virus enzyme maturation

Abstract: The cellular chaperone, HSP90, is identified here as an essential factor for the activity of NS2͞3 protease of hepatitis C virus. The cleavage activity of NS2͞3 protease synthesized in reticulocyte lysate is ATP-dependent, as evidenced by ATP depletion experiments and inhibition with nonhydrolyzable ATP analogs. Geldanamycin and radicicol, ATP-competitive inhibitors of the chaperone HSP90, also inhibit the cleavage of in vitro-synthesized NS2͞3. Furthermore, these HSP90 inhibitors prevent NS2͞3 cleavage when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 37 publications
1
58
0
1
Order By: Relevance
“…We observed no significant suppression of FHV RdRp activity in vitro with up to 50 M geldanamycin (Fig. 3A, lane 4), a concentration well above levels previously shown to suppress Hsp90 activity in vitro (20,54,57), 10-fold higher than that used in cellular assays ( Fig. 1 and 2), and approximately 3,500-fold above the IC 50 for geldanamycin and FHV RNA replication in infected cells (Fig.…”
Section: Vol 79 2005supporting
confidence: 45%
See 1 more Smart Citation
“…We observed no significant suppression of FHV RdRp activity in vitro with up to 50 M geldanamycin (Fig. 3A, lane 4), a concentration well above levels previously shown to suppress Hsp90 activity in vitro (20,54,57), 10-fold higher than that used in cellular assays ( Fig. 1 and 2), and approximately 3,500-fold above the IC 50 for geldanamycin and FHV RNA replication in infected cells (Fig.…”
Section: Vol 79 2005supporting
confidence: 45%
“…We used cerulenin, a fatty acid synthetase inhibitor previously shown to suppress positivestrand RNA virus replication (16,36), as a positive control. We chose initial inhibitor concentrations of 50 M cerulenin, 5 M geldanamycin, and 5 M radicicol on the basis of published studies of cultured cells that maximized target inhibition and minimized cellular toxicity (16,20,23,36,54). None of the inhibitors significantly reduced S2 cell viability during a 24-h incubation, although both geldanamycin and cerulenin reduced cell proliferation such that by 24 h cell recovery was 50 to 60% of control levels (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Another study demonstrated that HSP90 is important for vaccinia virus growth in cultured cells through interaction with viral core protein 4a (Hung et al, 2002). HSP90 is required to maintain the function of hepatitis B virus reverse transcriptase (Hu et al, 2004) and the enzyme maturation of hepatitis C virus (Waxman et al, 2001). Recently, HSP90 was also found to be a component of the dengue virus receptor complex in human cells and participated in the entry of the virus (Reyes-Del Valle et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of NS2/3 degradation has yet to be elucidated, it is likely that cellular proteins are involved. Cellular factors have also been proposed to be required for efficient NS2/3 protease activity (20,22), and the availability of these factors may modulate the degree of NS2/3 cleavage over the course of infection. In addition, the NS2/3 cleavage products themselves could potentially be involved in the regulation of these processes through their actions on host cellular proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis studies have identified His 952 and Cys 993 within NS2 as being essential for NS2/3 protease activity (15,16), and in addition, mutations thought to perturb the local conformation of the cleavage site also inactivate the enzyme (21). Furthermore, molecular chaperones have been proposed to be required for efficient cleavage at the NS2/3 site (22).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%